A socio-ecological framework supporting catchment-scale water resource stewardship. Issue 91 (January 2019) - Everard, Mark
Highlights: Water resource management exemplifies many resource challenges in a 'full world'. Reversing socio-ecological degradation resulting from overexploitation is essential. Ecosystem service assessment exposes benefits, externalities and mitigation options. Hybridising engineered & ecosystem-based approaches can rebuild catchment functions. A new integrated water resource stewardship (IWRS) paradigm includes regeneration. Abstract: The need to adapt human resource demands to the renewable capacities of ecosystems is widely acknowledged and has been transposed into multiple international and national commitments and strategies. This need is intensified by the contemporary öfull world' and increasing human numbers, urbanisation and climate change. However, resource exploitation models, markets and legacy regulations still tend to perpetuate an öempty world' model, separating societal demands from environmental capacity. Water resource management exemplifies many natural resource challenges. Choice of water management technologies still tends to maximise the efficiency of resource extraction and diversion to areas of high demand and economic influence, without necessarily prioritising the sustainability of the foundational natural capital of catchment ecosystems and the multiple benefits they provide to a diversity of co-dependents. Setting the impacts of technology choices within the conceptual framework of catchment ecosystem services forms a novel basis for recognising the often overlooked or disregarded externalities of differing types of water management techniques. It also provides insights into means to mitigate and sustainably hybridise qualitatively differing water management approaches to safeguard, and ideally to rebuild where degraded, the capacities of catchments to meet human needs on an enduring and equitable basis.